Dimeric and polymeric IgA, but not monomeric IgA, enhance the production of IL-6 by human renal mesangial cells - T. J. F. Reterink; W. E. M. Schroeijers; L. A. van Es; M. R. Daha (Hindawi Limited, 1996)
Depositions of IgA in the renal glomerular mesangial area are a hallmark of IgA nephropathy, and are thought to be crucial for the onset of inflammation processes in IgA nephropathy. In this report we show that human mesangial cells (MC) in vitro bind IgA and that binding of IgA enhances the production of IL-6 by MC. Furthermore we show that the size of IgA is crucial in its capability to enhance IL-6 production. Monomeric IgA does not affect basic IL-6 production, whereas dimeric and polymeric IgA enhance IL-6 production up to 3- to 9-fold respectively. Additional studies demonstrate that enhanced IL-6 production by MC is not accompanied by increased proliferation of human mesangial cells, a finding which is distinct from that found with rat mesangial cells. Taken together, these fmdings suggest that deposition of dimeric and polymeric IgA in the mesangial area of human kidneys in IgA nephropathy may amplify local inflammation.